Pelvic organ prolapse – causes, diagnosis, symptomatology and treatment - Rechberger, Tomasz; Bartuzi, Aleksandra; Perżyło, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2011)
Pelvic organ prolapse (POP) affects almost 50% of peri- and postmenopausal women and this condition is one of the main reasons for surgical treatment in this period of women’s life. The aetiology of pelvic floor dysfunction is multifactorial, but vaginal birth and aging (decrease of oestrogen levels and changes in the structure of connective tissue) are the most important risk factors for POP. Patient examination includes evaluation of POP stage using the Pelvic Organ Prolapse Quantification (POP-Q) scale as well as functional disorders (bladder and/or bowel dysfunctions) caused by the disease and its influence on the woman’s quality of life. Depending on the severity of POP and patient preference we can offer either conservative therapy (pelvic floor muscle training, electrostimulation or vaginal pessaries) or surgical treatment. Currently vaginal hysterectomy is not a standard procedure in patients suffering from POP. This type of surgery is considered only when additional indications are present. Nowadays the mainstay of surgical treatment is reconstructive surgery with synthetic grafts (polypropylene tapes or meshes – type I according to the Amid classification) inserted by a vaginal approach which reinforce damaged pelvic fascias and ligaments. The main goal of this type of surgery is to restore not only the appropriate anatomical conditions but also functions of pelvic floor organs.